2020
DOI: 10.1002/marc.202000449
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Mechanochromic Response in the High Strain Rate Uniaxial Compression of Spiropyran Embedded Silicone Elastomers

Abstract: The molecular processes that accompany dynamic mechanical response to large deformations at high strain rate (≈1000 s−1 or higher) underlie the early stages of damage in materials, but understanding of material response in this regime is typically limited to macroscopic constitutive equations. Here, spiropyran mechanophores are embedded in very short, stress‐bearing strands in silicone elastomers, and their mechanochromic response to uniaxial compression is explored in a Split Hopkinson Pressure (or Kolsky) Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…High strain rate compression was also employed to study its effect on activation of SP cross‐linked elastomers. [ 156 ]…”
Section: Sources Of Mechanical Forcementioning
confidence: 99%
See 2 more Smart Citations
“…High strain rate compression was also employed to study its effect on activation of SP cross‐linked elastomers. [ 156 ]…”
Section: Sources Of Mechanical Forcementioning
confidence: 99%
“…Exceptionally, a more recent study suggested that an extremely high strain rate (1000 s −1 ) of compression led to the onset activation of SP‐PDMS elastomer at a lower strain but a higher stress. [ 156 ] It was hypothesized that the critical strain achieved on the bulk matrix dominated the colorimetric onset because the stress was concentrated in a small region of SP containing strands.…”
Section: Factors Influencing Mechano‐responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 ] For example, in spiropyran‐containing polymers, mechanochemical ring opening reaction causes the transition of colorless spiropyran form into a colored merocyanine one, resulting in significant mechano‐optical response. [ 11,12 ] The photoinduced Z‐form of the azobenzene groups of azobenzene‐containing materials [ 13 ] can be successfully transformed into the initial E‐form upon stretching of the polymer film. [ 14 ] This process is accompanied by changes the ordering of molecules in the material and leads to a modification in its optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] In their communication, Stephen L. Craig and co‐workers report how the strain rate affects the activation of such spiropyrans in silicone elastomers. [ 10 ] Guillaume De Bo and co‐workers report a new mechanoresponsive fluorescent hydrogen‐bonded rotaxane based on a maleimide dye and demonstrate its force‐sensing properties in a synthetic model of living tissue. [ 11 ] Ester Verde‐Sesto, José A. Pomposo and co‐workers review on techniques that can be used to manipulate and mechanically activate single‐chain molecules and thus allow one to elucidate information on the stress‐induced response of individual mechanophores and polymer molecules.…”
mentioning
confidence: 99%